An Islamic point of view of cryptocurrency investment: Generations z fear of missing out (FOMO) and their personal traits as traders - Rahayu, Nurul Widyawati Islami; Hepni; Fauzan; Poernomo, Djoko; Dafik; Mursyidah, Indah Lutfiyatul; Jannah, Excelsa Suli Wildhatul (Edelweiss Applied Science and Technology, 2024)
The rise of cryptocurrency has sparked a global financial revolution, captivating the interest of various demographics, including the digitally savvy Generation Z. This study explores the Islamic perspective on cryptocurrency investment, focusing particularly on the intersection of Generations Z Fear of Missing Out (FoMO) and their personal traits of traders. Within Islamic finance, which emphasizes ethical investing and prohibits speculative activities akin to gambling, cryptocurrency presents a unique challenge. The rapid appreciation of digital currencies and the pervasive influence of social media amplify FoMO among young investors, driving them to partake in high-risk ventures. This behavioral inclination often conflicts with Islamic principles, which advocate for risk-sharing and tangible asset-backed transactions. The study delves into how Generations Z psychological predispositions, such as overconfidence, risk tolerance, and the allure of quick gains, align or clash with Islamic ethical standards. It examines the potential for educational interventions to reconcile these differences by promoting financial literacy that aligns with Sharia law. Additionally, the study addresses the broader implications of these trends on the development of Islamic financial products tailored to digital assets, aiming to bridge the gap between religious adherence and modern investment opportunities. This research highlights the necessity for a nuanced understanding of Generations Z investment motivations and the importance of integrating Islamic ethical considerations into the evolving landscape of cryptocurrency. The method used in this study is a mixed method, namely a combination of quantitative and qualitative methods. The quantitative method is used to analyze multi-time series forecasting on Generations Z fear of missing out (FoMO) and their personal traits as traders. While the qualitative method is used to analyze the results of an in-depth interview and find the potential conflicts with Islamic principles advocating for minimum transaction risk and for the use tangible asset-backed transactions. The results suggest that generation Z becomes more immersed in digital and social media landscapes, their susceptibility to FoMO intensifies, driving more frequent and sometimes impulsive trading behaviours. Concurrently, as these young investors gain more experience and exposure to the cryptocurrency market, their personal traits such as risk tolerance, adaptability, and tech-savviness also evolve, potentially leading to more sophisticated trading strategies. However, these practices conflict with Islamic point of view.